ChemInform Abstract: A Versatile Domino Process for the Synthesis of Substituted 3‐Aminomethylene‐chromanones and 2‐Pyridones Catalyzed by CsF. Issue 37 (22nd August 2013) - Pintiala, Catalin; Lawson, Ata Martin; Comesse, Sebastien; Daich, Adam
Abstract Addition reaction of amines to substrate (I) is followed by pyran ring opening which leads in the next step to the desired pyridone structure and/or an unexpected 3‐aminomethylene chromanone product.